Melanin and Curls: Evaluation of Black Women Candidates. (September 2019) - Lemi, Danielle Casarez; Brown, Nadia E.
Abstract: Research on candidate evaluation has delved into questions of how voters evaluate women candidates, Black male candidates, as well as how candidates' appearances may condition electoral opportunities. Combined, this scholarship has tended to focus on how race, gender, and skin tone privilege or undermine evaluations of Black male or White women candidates. We intervene to study Black women candidates and draw on research on colorism and Black women's hairstyles and ask: How does variation in skin tone and hairstyle affect Black voter evaluations of Black women candidates? We develop and test two hypotheses: the empowerment hypothesis and the internal discrimination hypothesis. We mostly find support for the latter. Importantly, we find that the interaction of dark skin and non-straight hair has mostly negative effects on Black men and women's trait evaluations, but a positive effect on Black women's willingness to vote for the candidate. Furthermore, this research shows that hair texture is an important aspect of responses to Black women candidates—hair is not just hair for Black women candidates. This research shows that understanding the effects of candidate appearance on voter behavior necessitates considering the intersection of racial and gender phenotypes.